Evaluasi Toksisitas Akut Kulit Batang Manihot esculenta Crantz. : Pendekatan In Silico dan In Vitro - Sida, Nurramadhani A. (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2025)
Manihot esculenta Crantz has been used in research focused on drug discovery and development. Although the compound content and pharmacological effects of this plant have been widely reported, it is necessary to conduct a toxicity evaluation when developing it as a potential drug candidate to determine its effectiveness and therapeutic potential. This study aims to evaluate the acute toxicity of stem bark of M. esculenta both in silico and in vitro. In-silico toxicology was conducted on 13 compounds using ProTox-II. The indicators assessed were LC50 and organ toxicity such hepatotoxic, carcinogenic, immunotoxicity, mutagenic, nephrotoxic, neurotoxic. The in vitro assay used BSLT with Artemia salina. The mortality percentage of A. salina was calculated to determine the LC50 value. The in-silico results showed five compounds Hydrocyanic acid, beta stigmasterol, 6'-Apiosyllotaustralin, Yucalexin B22, and Yucalexin B14 with a toxicity category of < 5. The in vitro results showed LC50 values for the ethanol and n-hexane fractions of 548.774 and 375.787 µg/mL, respectively. Further in vivo toxicity testing is needed to provide additional evidence of the toxicity of M. esculenta stem bark. The stem bark of M. esculenta is toxic depending on the concentration, with compounds such as hydrocyanic acid, beta stigmasterol, 6'-Apiosyllotaustralin, Yucalexin B22, and Yucalexin B14 suspected to play an important role in the toxic effects.